2002
DOI: 10.1037/0096-3445.131.4.594
|View full text |Cite
|
Sign up to set email alerts
|

Object substitution without reentry?

Abstract: (2002) used computer simulations to claim that many current models of metacontrast masking can account for the findings of V. Di Lollo, J. T. Enns, and R. A. Rensink (2000). They also claimed that notions of reentrant processing are not necessary because all of V. Di Lollo et al. 's data can be explained by feed-forward models. The authors show that G. Francis and F. Hermens's claims are vitiated by inappropriate modeling of attention and by ignoring important aspects of V. Di Lollo et al. 's results.We note … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…And there is evidence that we tend to perceive the world as a collection of discrete objects (e.g., Rosch et al, 1976;Di Lollo, Enns, & Rensink, 2002). It has been suggested that visual recognition involves an intermediate part-based representation, between elementary features and objects (Biederman, 1987).…”
Section: Faces and Words Are Recognized By Partsmentioning
confidence: 99%
“…And there is evidence that we tend to perceive the world as a collection of discrete objects (e.g., Rosch et al, 1976;Di Lollo, Enns, & Rensink, 2002). It has been suggested that visual recognition involves an intermediate part-based representation, between elementary features and objects (Biederman, 1987).…”
Section: Faces and Words Are Recognized By Partsmentioning
confidence: 99%
“…Although we disagree with many of the comments in Di Lollo et al (2002), in this article, we explore a more direct test of the ability of the models to explain the properties of backward masking. We also consider the model proposed by Di and explore how well it generalizes to backward-masking conditions.…”
mentioning
confidence: 98%
“…In a reply to the comments of Francis and Hermens (2002), Di Lollo, Enns, and Rensink (2002) argued that the models were inappropriately applied to their data. Although we disagree with many of the comments in Di Lollo et al (2002), in this article, we explore a more direct test of the ability of the models to explain the properties of backward masking.…”
mentioning
confidence: 99%
“…Some researchers have taken the stand that certain experimental findings rule out feed forward models (Di Lollo, Enns, & Rensink, 2000, 2002). This topic deserves some additional discussion because, contrary to common belief, such debates rarely help drive model development.…”
Section: Model Structure and Computationmentioning
confidence: 99%